EVALUATION OF INTRA-RENAL BLOOD FLOW PARAMETERS IN PATIENTS WITH RENAL FIBROMUSCULAR DYSPLASIA - THE POLISH REGISTRY FOR FIBROMUSCULAR DYSPLASIA (ARCADIA-POL STUDY). (June 2018) - Januszewicz, M.; Michalowska, I.; Warchol-Celinska, E.; Aniszczuk-Hybiak, A.; Ziebka, J.; Florczak, E.; Witkowski, A.; Kadziela, J.; Kabat, M.; Klisiewicz, A.; Dobrowolski, P.; Tykarski, A.; et al.
Abstract: Objective: To assess intra-renal blood flow parameters in patients with renal fibromuscular dysplasia (FMD) in patients with renal FMD enrolled to ARCADIA-POL study. Design and method: We analyzed 143 patients with renal FMD enrolled in the ARCADIA-POL study since 2015 (Polish-French collaboration). All patients underwent evaluation including ABPM, biochemical evaluation, biobanking, duplex Doppler of carotid and abdominal arteries and whole body angio-CT. We divided patients with renal FMD into two groups – 31 patients with significant renal artery stenosis (RAS) (26F, 5 M, mean age:19.8 ± 12.7 years) and 112 patients with non-significant RAS (93 F, 19 M, mean age:47.2 ± 14.9 years). We compared those two groups to the matched control groups – 60 normotensive individuals (44F, 16 M, mean age:42.5 ± 9.1 years) and 60 patients with primary hypertension (40F, 20 M), mean age: 43.3 ± 11.4 years. Results: FMD patients with non-significant RAS, FMD patients with significant RAS, normotensives and patients with primary hypertension differed significantly in resistive indexes values (RI) (0.59 ± 0.08 vs 0.53 ± 0.09 vs 0.61 ± 0.06 vs 0.62 ± 0.06, respectively p < 0.001; FMD patients with significant RAS vs normotensives: p < 0.001; vs patients primary hypertension: p < 0.001). In patients with FMD with significant RAS there was a significant correlation between RI and IMT (r = −0.658; p = 0.008). Subsequently we performed analysis "per kidney" and we compared three groups of renal arteries in FMD patients-renal arteries with no FMD lesions (n = 75), renal arteries with FMD with non-significant RAS (n = 180) and renal arteries with FMD with significant RAS (n = 31). FMD renal arteries with significant RAS were characterized by lower RI value, higher maximal blood flow velocity (Vmax), higher renal aortic ratio (RAR) and higher acceleration time (AT) as compared to both FMD renal arteries with non-significant RAS and renal arteries with no FMD lesions. No differences in intra-renal blood flow parameters were found between FMD renal arteries with non-significant RAS and renal arteries with no FMD lesions. Conclusions: Our results indicate that FMD patients with significant RAS are characterized by changes in intra-renal blood flow parameters as those observed in atherosclerotic RAS. Moreover those changes were related to carotid arteries IMT.